DNA Data Storage and Hybrid Molecular–Electronic Computing - Carmean, Doug; Ceze, Luis; Seelig, Georg; Stewart, Kendall; Strauss, Karin; Willsey, Max (Proceedings of the IEEE, 2018)
Moore's law may be slowing, but our ability to manipulate molecules is improving faster than ever. DNA could provide alternative substrates for computing and storage as existing ones approach physical limits. In this paper, we explore the implications of this trend in computer architecture. We present a computer systems perspective on molecular processing and storage, positing a hybrid molecular-electronic architecture that plays to the strengths of both domains. We cover the design and implementation of all stages of the pipeline: encoding, DNA synthesis, system integration with digital microfluidics, DNA sequencing (including emerging technologies such as nanopores), and decoding. We first draw on our experience designing a DNA-based archival storage system, which includes the largest demonstration to date of DNA digital data storage of over three billion nucleotides encoding over 400 MB of data. We then propose a more ambitious hybrid-electronic design that uses a molecular form of near-data processing for massive parallelism. We present a model that demonstrates the feasibility of these systems in the near future. We think the time is ripe to consider molecular storage seriously and explore system designs and architectural implications.